(untitled) (Fiep Bulletin - online, 2015)
This work was developed in the Company Paranaense De Energia COPEL in the sector of distribution of the AGCEL - Agency of Cascavel/Pr. It had as objective to map the ergonomic conditions of the workers with function of electricians. They had been searched 100% of the professionals who were acting of June of 2003 the December of 2004; divided in two samples, being the first one of 20 and second of 7 electricians. As methodology it was used ergonomic analysis of the work. The used instruments had been: accompaniment and direct comment, anthropometrics interviews, photographs, measures, to weighed of equipment of the individual and collective security. The posture unsuitable in the activities, the great physical requirement of the work and the relation of the increase of pain with the time of service in the same activity had been verified. One evidenced that from 11 years in function 100% of the searched ones they were acting with pains; observing then the necessity of intervention and preventive training.